The Effect of Profitability, Dividend Policy and Inflation on Minimizing Risk with Investment Decision as Intervening Variable in Manufacturing Firms Listed on The Indonesian Stock Exchange - Thania Desrika; Yuhani Ladewi; Junaidi Junaidi (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2026)
This study examines the effects of profitability, dividend policy, and the inflation rate on investment decisions and risk minimization in manufacturing companies from various industrial sectors listed on the Indonesia Stock Exchange (IDX). A quantitative descriptive approach was used. The study involved 67 listed companies, with a purposive sample of 12, yielding 60 financial statement observations. Secondary data were collected from the company's financial reports. Data were analyzed using descriptive statistics and Partial Least Squares-Structural Equation Modeling (PLS-SEM), including outer and inner model analyses, hypothesis testing, and mediation analyses. The results indicate that profitability and dividend policy have significant positive effects on investment decisions, while the inflation rate has no significant effect. Profitability and investment decisions significantly contribute to risk minimization, whereas dividend policy and the inflation rate do not. Furthermore, investment decisions mediate the relationship between profitability and risk minimization but do not mediate the effects of dividend policy or the inflation rate on risk minimization.